Synthetic Strategies Toward Nitrogen-Rich Energetic Compounds Via the Reaction Characteristics of Cyanofurazan/Furoxan - Wang, Luoluo; Zhai, Lianjie; She, Weiqing; Wang, Minchang; Zhang, Junlin; Wang, Bozhou (Frontiers in Chemistry, 2022)
The structural units of amino/cyano substituted furazans and furoxans played significant roles in the synthesis of nitrogen-rich energetic compounds. This account focused on the synthetic strategies towards nitrogen-rich energetic compounds through the transformations based on cyanofurazan/furoxan structures including 3-amino-4-cyanofurazan, 4-amino-3-cyano furoxan, 3,4-dicyanofurazan and 3,4-dicyanofuroxan. The synthetic strategies towards seven kinds of nitrogen-rich energetic compounds, such as azo (azoxy)-bridged, ether-bridged, methylene bridged, hybrid furazan/furoxan-tetrazole based, tandem furoxans based, hybrid furazan-isofurazan based, hybrid furoxan-isoxazole based and fused framework based energetic compounds were fully reviewed, with corresponding reaction mechanisms towards the nitrogen-rich aromatic frameworks and examples of using the frameworks to create high energetic substances were highlighted and discussed. The energetic properties of typical nitrogen-rich energetic compounds had also been compared and summarized.